2018
DOI: 10.1039/c8ew00029h
|View full text |Cite
|
Sign up to set email alerts
|

Link between dissolved organic matter transformation and process performance in a membrane bioreactor for urinary nitrogen stabilization

Abstract: MBR instabilities during urinary nitrogen stabilization could be identified and explained using 3DEEM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…Also, a high resolution (±0.1 kPa) pressure sensor (Keller, Reinacherstrasse, Basel, Switzerland) was installed to monitor the TMP, ensuring a sub-critical flux operation to avoid fouling of the UF module. Given the high fouling potential of urine (Jacquin et al, 2018), the UF module was operated at a flux of about 0.5 L.m -2 .h -1 which led to low TMP development (3.2 ± 2.3 kPa) which obviously is not an optimised operational flux. The MLSS of the reactor was measured weekly and maintained to approximately 5 ± 1 g.L -1 that allowed to keep the MLSS/MLVSS ratio above 0.85.…”
Section: Nitrification Membrane Bioreactor Start-up and Operationmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, a high resolution (±0.1 kPa) pressure sensor (Keller, Reinacherstrasse, Basel, Switzerland) was installed to monitor the TMP, ensuring a sub-critical flux operation to avoid fouling of the UF module. Given the high fouling potential of urine (Jacquin et al, 2018), the UF module was operated at a flux of about 0.5 L.m -2 .h -1 which led to low TMP development (3.2 ± 2.3 kPa) which obviously is not an optimised operational flux. The MLSS of the reactor was measured weekly and maintained to approximately 5 ± 1 g.L -1 that allowed to keep the MLSS/MLVSS ratio above 0.85.…”
Section: Nitrification Membrane Bioreactor Start-up and Operationmentioning
confidence: 99%
“…The seed sludge was collected from a wastewater treatment plant (Central Park Sydney, Ultimo, NSW, Australia) and, for the first 20 weeks of operation, the sludge was gradually acclimatised to the new substrate. As the salinity, C/N ratio and pH of urine differed significantly from municipal wastewater, urine was initially diluted 100 times and the pH corrected to 7 by addition of HCl (Fumasoli et al, 2016;Jacquin et al, 2018;Udert and Wächter, 2012). Following the increase in the abundance and activity of ammonia and nitrite oxidising bacteria (AOBs and NOBs), estimated through the amount of NO3produced per gram of MLSS, urine dilution was gradually decreased.…”
Section: Nitrification Bioreactormentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, NH 3 is alkaline, volatile and toxic at high concentrations [3]. While several articles have shown that aerobic biological nitrification of urine is possible [49,85,86], until 2018 it was unclear whether the microbial consortium could survive the level of radiation and gravity on the ISS. However, in 2018, a research team sent a nitrifying microbial consortium on a 44-day FOTON-M4 flight to Low Earth Orbit (LEO) and exposed it to 10 −3 -10 −4 g (gravitational constant) and 687 ± 170 µGy (Gray) d −1 (20 ± 4 • C), exposing them to about double the radiation level of that on the ISS [87].…”
Section: Melissa Projectmentioning
confidence: 99%
“…As discussed in the earlier part of this section, the variation in SMPs detected along the depth of UASB reactors suggested that the microorganisms that carry out fermentation and the methanogens might play different roles in terms of SMPs; the former appearing to contribute more to its production, while the latter more to its consumption (Wu & Zhou, 2010;Zhou et al, 2009). (Jacquin et al, 2018) studied the changes in the dissolved organic content in an activated sludge membrane bioreactor system with a high nitrogen concentration in the influent (urine) using three-dimensional excitation-emission spectroscopy, and liquid chromatography coupled to organic carbon and nitrogen detection (LC-OCD) and UV absorption spectroscopy at 254 nm. The concentrations of humic substances, acidic and neutral low molecular weight organic compounds were found to have significantly reduced (62% to 84% in general) inside of the MBR as compared to the influent; it was explained that these compounds largely underwent biotransformation.…”
Section: Untargeted Analysismentioning
confidence: 95%